Report for the period July 2009 - Dec 2009 : (human resource development, health and HIV/AIDS) (CCS (Georgetown)GY, 2010)
Highlights the Directorate's activities in the fields of human resource development, health and HIV/AIDS.
Prepared for the Hon. Dr. Denzil Douglas...in preparation for the Twenty-first Inter-sessional Meeting of the Conference of Heads of Government, Dominica, 11-12 March, 2010